Alloying Pd with Ru enables electroreduction of nitrate to ammonia with ∼100% faradaic efficiency over a wide potential window - Hu, Yue (2024)
Electrocatalytic nitrate (NO3-) reduction reaction (eNO3-RR) to ammonia under ambient conditions is deemed a sustainable route for wastewater treatment and a promising alternative to the Haber-Bosch process. However, there is still a lack of efficient electrocatalysts to achieve high NH3 production performance at wastewater-relevant low NO3- concentrations. Herein, we report a Pd74Ru26 bimetallic nanocrystal (NC) electrocatalyst capable of exhibiting an average NH3 FE of ∼100% over a wide potential window from 0.1 to -0.3 V (vs. reversible hydrogen electrode, RHE) at a low NO3- concentration of 32.3 mM. The average NH3 yield rate at -0.3 V can reach 16.20 mg h-1 cm-2. Meanwhile, Pd74Ru26 also demonstrates excellent electrocatalytic stability for over 110 h. Experimental investigations and density functional theory (DFT) calculations suggest that the electronic structure modulation between Pd and Ru favors the optimization of NO3- transport with respect to single components. Along the *NO3 reduction pathway, the synergy between Pd and Ru can also lower the energy barrier of the rate-determining steps (RDSs) on Ru and Pd, which are the protonation of *NO2 and *NO, respectively. Finally, this unique alloying design achieves a high-level dynamic equilibrium of adsorption and coupling between *H and various nitrogen intermediates during eNO3-RR.